Immune checkpoint blockade for unresectable or metastatic uveal melanoma: A systematic review. - Heppt, Markus V.; Steeb, Theresa; Schlager, Justin Gabriel; Rosumeck, Stefanie; Dressler, Corinna; Ruzicka, Thomas; Nast, Alexander; Berking, Carola (Cancer Treatment Reviews, 2017)
The use of immune checkpoint blockade (ICB) for uveal melanoma (UM) is little established. The aim of this review was to provide a comprehensive overview on the efficacy, safety, and tolerability of ICB in patients with UM.We performed a systematic literature research covering MEDLINE, Embase and CENTRAL. Abstracts of pertinent conferences and trial registers were handsearched for relevant studies.Out of 1327 records initially identified, 12 eligible studies were included in the qualitative synthesis. They comprised 7 expanded access or named patient programs (n=162), 4 phase II trials (n=171), and 1 phase Ib trial (sample size unknown), while no randomized controlled trial was found. Ipilimumab monotherapy was assessed at 3mg/kg in 5 trials (n=186) with a response rate of 0 to 5%. Two reports investigated ipilimumab at 10mg/kg (n=45) with radiological responses observed in 0 to 6.5%. The median progression-free survival (PFS) was below 3months and the median overall survival was 5.2-9.8months for ipilimumab monotherapy. Severe immune-related adverse events occurred at a frequency comparable to cutaneous melanoma (6 to 36%). Two studies investigated pembrolizumab (2mg/kg) and nivolumab (3mg/kg) with overall response rates of 30% and 6%, respectively. Data on combined ipilimumab and programmed cell death protein 1 inhibition were available from one expanded access program, but no response was observed with a median PFS of 2.9months.UM is little responsive to ipilimumab regardless of dosage schemes. Sound randomized clinical trials are needed to evaluate the efficacy of combined ICB in patients with UM.
EVALuna2:154325